The quality of Tibetan sheep meat from pastures was synergistically regulated by the rumen microbiota and related genes at different phenological stages - Chen, Xiaowei; Sha, Yuzhu; Liu, Xiu; He, Yanyu; Li, Wenhao; Yao, Liangwei; Wang, Jiqing; Yang, Wenxin; Chen, Qianling; Gao, Min; Huang, Wei; Ma, Bin (Frontiers in Veterinary Science, 2025)
Meat quality is a key indicator of meat performance in ruminants, and its mechanism and regulation are also key to ruminant research. Studies have shown that animal meat quality is related to the gut microbiota. In this study, RT-qPCR and 16S omics were employed to assess meat quality and intestinal microbiota. The objective was to investigate the influence of seasonal variations on the meat quality of Tibetan sheep ewes by examining the rumen microflora, meat quality attributes, and associated gene expression profiles over three distinct months: May, August, and December.The results indicate that muscle tenderness was significantly greater (p < 0.001) in the grass period than in the regrowth and dry grass periods and was highest in the longest dorsal muscle. The cooking rate of the foreleg muscle was significantly greater (p < 0.05) than that during the regrowth and dry grass periods, and the pH24h significantly differed (p < 0.05) across the different seasonal periods. The crude protein content of the longest back muscle and the foreleg muscle was significantly greater (p < 0.001) than that of the wither and grass stages during the regrowth period and slightly decreased during the grass stage. The crude fat and crude ash contents of the three groups differed significantly, and the fat content during the grass stage was significantly (p < 0.05) greater than that during the regrowth stage and the wither stage. Expression analysis of genes related to meat quality revealed that the expression of the ADSL gene was significantly greater (p < 0.05) in the anterior and posterior leg muscles during the grass period than during the regrowth and wilting periods, whereas the expression of the FABP3 gene was lower than that during these two periods. Correlation analysis revealed that Rikenellaceae_RC9_gut_group was significantly positively correlated (p < 0.05) with shear forceand cooked meat percentage and significantly negatively correlated (p < 0.05). Ruminococcus and Butyrivibrio were significantly positively correlated (p < 0.05) with CAST and highly significantly positively correlated (p < 0.05). In conclusion, meat quality during different seasons is regulated by the rumen microbiota and their associated genes.